Engaged Journalism and News Work: A Sociotechnical Analysis of Organizational Dynamics and Professional Challenges. (27th May 2020) - Schmidt, Thomas R.; Lawrence, Regina G.
ABSTRACT: Building upon the sociotechnical perspective presented by Lewis and Westlund (2015, "Actors, Actants, Audiences, and Activities in Cross-media News Work: A Matrix and a Research Agenda." Digital Journalism 3 (1): 19–37. doi:10.1080/21670811.2014.927986 ), this study examines organizational dynamics, technological affordances and professional challenges of engaged journalism practices by analyzing how Hearken, one of the most celebrated audience engagement companies, and its tools and services are being implemented in 15 U.S. news organizations. This framework identifies Hearken and organizations like it as important "external actors" providing technological "actants" that are shaping how newsrooms report the news by providing ways for audiences to be brought into producing the news, particularly during the earlier phases of the reporting process. Based on in-depth interviews, we find that nearly every news organization in our sample reports some measure of success by using Hearken for involving audience members throughout the production of news. At the same time, we also identify how this implementation is significantly shaped by organizational imperatives and the models particular organizations create for producing audience-centric news work. Ultimately, this study presents a partial update to the decades-long literature on participatory journalism by suggesting that engaged journalism practices actually create opportunities for meaningful audience involvement.